Predictors of renal outcome in ANCA-assosiated glomerulonephritis - Ljubičić Bojana; Azaševac Tijana; Popović Milica; Živković Siniša; Božić Dušan; Ćelić Dejan (Vojnosanitetski Pregled)
Backgraund/Aim. Primary anti-neutrophil cytoplasmatic antibody (ANCA)-associated vasculitis are chronic multisystemic autoimmune diseases which include microscopic polyangitis (MPA), granulomatosis with polyangitis (WG), eosinophilic granulomatosis with polyangitis (EPGA; churg-strauss syndrome – CSS), and also a localized forms of ill-ness. In our research, we studied clinical and serological parameters in patients, in order to find out which of them would be the best predictor of renal outcome in ANCA-associated vasculitis. Methods. Data from 42 patients with diagnose of MPA (9), WG (17), EPGA (0), CSS (0), and al-so idiopathic rapidly progressive glomerulonephritis (ROEB) without immune deposits (renal-limited vasculitis – 16) were analyzed. Cockroft formula was used for calculating the glomerular filtration in the moment of presenting the illness, and also after five year follow-up period. Other factors that were analyzed are: gender, age, type of ANCA antibodies, type of infections, stage of chronic kidney dis-ease, need for heamodialysis and mortality. Results. Of a total of 42 patients, 17 (40.48%) were male. The average age of the patients at the time of diagnosis was 57.8 (± 10.44) years. Seventeen patients (40.48%) had a diagnosis of WG, 9 (21.43%) MPA, and 16 (38.09%) iRPGN. The presence of positive anti-proteinase (anti-PR3) antibodies was confirmed i n 1 8 patients, a nd a nti-MPO antibodies in 17 patients. Three patients had both subtypes of ANCA antibodies (anti-PR3 and anti-MPO). Initially, 12 patients required heamodialysis treatment. Twenty nine patients had a complete and 13 patients had partial remission. Out of the total number of patients, 8 patients (19.04%) developed the terminal renal failure stage, and ended up on a chronic dialysis program. During a five-year follow-up period, 12 patients (28.57%) resulted in death. The age of the patient proved to be statistically significant predictor of glomerular filtration rate (GFR) at the moment of presentation of the disease (p = 0.011). GFR t = 0 was statistically significant (p = 0.000) for the evaluation of kidney function outcomes in ANCA-associated glomerulonephritis. Conclusion. Kidney function in the moment of illness presentation, determined by GFR t = 0, is the most important significant factor for predicting renal outcome in ANCA-associated vasculitis, and also the mortality in these patients.